Emergence of sliding ferroelectricity in naturally parallel-stacked multilayer ReSe2 semiconductor - Wuhong Xue; Peng Wang; Wenjuan Ci; Ying Guo; Jingyuan Qu; Zeting Zeng; Tianqi Liu; Ri He; Shaobo Cheng; Xiaohong Xu (Nature Communications)
Abstract Sliding ferroelectric semiconductors can advance the applications of slidetronics in silicon-compatible microelectronic and optoelectronic devices for the post-Moore era. However, traditional sliding ferroelectrics typically require complex artificial stacking to break symmetry, and most of them lack atomic-scale evidence. Here, we report a sliding ferroelectric semiconductor of naturally parallel-stacked ReSe2 with layer number N ≥ 3 through rational sliding approach, which is different from the reported sliding ferroelectrics with N ≥ 2. This sliding ferroelectricity avoids the rigorous artificially stacking design. The origin of ferroelectricity arises from the fact that the sliding of arbitrary middle atomic layer breaks the spatial inversion symmetry. We also directly measure the polarization value of ReSe2 by polarization-electric field hysteresis. Additionally, the electro-tunable ferroelectric polarization is further confirmed by microscopic ferroelectric switching. And, the sliding ferroelectricity enables switchable ferroelectric diode and programmable photovoltaic effect. Our study sheds light on the exploration of sliding ferroelectric semiconductors in naturally parallel-stacked configurations.